KOMPETENSI KEPRIBADIAN GURU DALAM MENINGKATKAN KEDISIPLINAN SISWA MAN 1 LAMONGAN - Yudis Nurrachman, M Alief; Sari Lestari, Egi; Melvi Febriyanti; Anni Amaliyatul ilmi (Universitas Islam Malang, 2024)
A school is a place where students can receive instruction formally in an organized environment that aims to help them achieve their academic and personal success. In addition to spreading knowledge, good teachers are also role models for their students by getting to know students more deeply. Therefore, good teacher character is very important in fostering student discipline because they have the ability to guide and limit students to act and think according to their personality development. This study discusses how teacher personality can affect in improving the discipline of MAN 1 Lamongan students. The purpose of this study was to identify how the personality of teachers in MAN 1 Lamongan impacts student behavior. This study used a qualitative descriptive approach, which involved observation, interviews, and documentation with a combination of data from primary and secondary sources. The results showed that the nature of a teacher greatly affects the level of discipline in the classroom. Positive teachers often show more self-control and obedience in their students than less charismatic teachers. Teachers who are fair, consistent, strong, powerful, and intelligent and compassionate will most likely improve the discipline of their students.